Pengaruh Orientasi Kewirausahaan, Kecepatan Masuk Pasar dan Keberlanjutan Usaha Keluarga (Studi pada Sub Sektor Kriya di Kecamatan Pahunga Lodu) - Anarato, Indah Sari; Situmorang, Tumpal Pangihutan (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to determine the influence of entrepreneurial orientation, speed of market entry and business performance on the sustainability of family businesses in Kaliuda village, Pahunga Lodu District. This research is a quantitative study with a population and sample of ikat weaving craftsmen in Pahunga Lodu District as well as respondents who are active in ikat weaving from generation 2 to generation 3. Data collection was carried out by distributing questionnaires to respondents. Data analysis used Structural Equation Modeling Partial Least Square (SEM-PLS) data analysis. The results of this research show that entrepreneurial orientation, speed of market entry and business performance have a significant effect on the sustainability of family businesses.